Optimisation of Analytical Method for Extraction and Chromatographic Analysis of Phenolic Compounds in Brewing Malts - Adámková, Karolína; Adam, Martin; Ventura, Karel (University of Novi Sad, 2016)
Phenolic compounds are one of the most biologically active substances with positive impact on the human health. These are substances of the plant origin protecting plants against adverse environmental effects. In their structure an aromatic ring containing one or more hydroxyl groups are occurring. These compounds are divided by the structure into groups known as flavonoids, phenolic acids, stilbenes and lignans. Beer is well known as a rich source of phenolic compounds from which 80% comes from malt. First part of this study is focused on the optimisation of chromatographic process to separate eleven phenolic substances using gradient elution. Optimized conditions of separation were furthermore used for analysis of phenolic substances in congress wort extracts, prepared from samples of barley and wheat malts. Samples of congress wort were brewed by well-defined procedure commonly used as standard methodology in brewing. Through the time of saccharification an amylolytic enzymes activity in malt is determined. Saccharification is tested 10 minutes after reaching the temperature point of mash at 70 °C through the iodine test. For pre-concentration of analytes from congress wort, the microextraction by packed sorbent method (MEPS) was chosen. The most used sorbents for MEPS are silica-based (C18, C8, C2, Silica, or mixed sorbent C8 + SCX). First experiments have confirmed that for tested compounds extraction, the C18 sorbent is the best choice. Choosing the MEPS method allowed not only minimisation of sample and solvents consumptions, but also pre-concentration and sampling in one-step. After separation by HPLC using gradient elution, target phenolic compounds were detected by diode array detector (DAD). Its advantage is that it could select the suitable wavelength for analysis of individual components. Second type of detector used in this study was electrochemical coulometric detector (ECD), which is selective for substances containing hydroxyl groups.
Optimalizace analytické metody pro extrakci a chromatografickou analýzu fenolických sloučenin v pivovarských sladech
Keywords: Phenolic compounds; HPLC; Brewing Malts; Worts; Fenolické sloučeniny; HPLC; Pivovarské slady; Sladiny